HEALTHY ORGANIZATIONAL PRACTICES IN SMES IN ECUADOR - Hinojosa, Deysi (Revista Arbitrada Formación Gerencial, 2024)
The objective of this research was to describe the healthy organizational practices implemented in SMEs in Ecuador. It is a descriptive research with field design, contemporary cross-sectional, in which a sample of 421 employees of SMEs in zone 5 of Ecuador was approached, using a checklist derived from the HEROCheck instrument (Salanova et al., 2019). The results report that the most frequent practices in SMEs are 1) Health and wellness programs, 2) Training and education programs in specific areas of work, 3) Newsletters, 4) Diversity and inclusion awareness and training for all employees, and 5) Performance evaluation and feedback. It is concluded that SMEs recognize that long-term organizational success depends on creating an environment in which employees feel valued, supported and motivated to actively contribute.